Blood Measurements: Microwaving Blood as a Non‐Destructive Technique for Haemoglobin Measurements on Microlitre Samples (Adv. Healthcare Mater. 4/2014). Issue 4 (April 2014) - Basey‐Fisher, Toby H.; Guerra, Nadia; Triulzi, Chiara; Gregory, Andrew; Hanham, Stephen M.; Stevens, Molly M.; Maier, Stefan A.; Klein, Norbert
<x xml:space="preserve">Abstract</x> The electric field component of the microwaves emanating from the dielectric resonator is able to penetrate the microfluidic channel, serum, and individual blood cells. Subsequently, it interacts with every hemoglobin molecule present within each red blood cell. On page 536, Toby H. Basey‐Fisher and team conclude that the dielectric contrast between water and hemoglobin means that a change in the hemoglobin concentration leads to a change in the microwave response. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>